Synthesis, characterization, and biological activities of a Cu(II) complex with the non-steroidal antiinflammatory drug flufenamic acid. Issue 20 (18th October 2017) - Sheng, Gui-Hua; Wang, Tian-Rui; Wang, Cun-Fang; Chen, Xiang-Fei; Ma, Zheng; Zhu, Hai-Liang; Zhou, Quan-Cheng
Abstract: [Cu II (L)2 .C12 H10 N2 ] with flufenamic acid (HL=C14 H10 F3 NO2 ) and phenanthroline (C12 H10 N2 O) was synthesized and characterized by C, H and N elemental analysis, single-crystal X-ray diffraction and, IR spectra. The urease inhibitory and antibacterial activities of the complex were tested. The complex showed strong inhibitory activity against jack bean urease with an IC50 value of 0.265 μM. Four bacteria, Bacillus subtilis, Escherichia coli, Staphylococcus aureus, and proteusbacillus vulgaris, were used in the antibacterial test . The complex showed strong inhibitory activity against the species with IC50 values of 2.016, 35.037, 10.680, and 3.820 μM. The interactions of the complex with human serum albumin (HSA) were studied through fluorescence spectroscopy. By analyzing the experimental data, we concluded that the fluorescence quenching mechanism of the complex with serum albumin was static quenching. The binding mode of the complex with DNA through UV spectroscopy was electrostatic binding or groove. Abstract :